1991
DOI: 10.1159/000125704
|View full text |Cite
|
Sign up to set email alerts
|

Naloxone Increases the Frequency of the Electrical Activity of Luteinizing Hormone-Releasing Hormone Pulse Generator in Long-Term Ovariectomized Rats

Abstract: Characteristic increases in neuronal activity accompanied by the initiation of each luteinizing hormone (LH) pulse have been successfully recorded in freely moving ovariectomized rats by means of multiunit activity (MUA) recording techniques. In the present study, the effect of the opioid receptor antagonist naloxone on this neuronal activity was examined in rats ovariectomized for 6–10 weeks. Electrodes were chronically implanted into the medial basal hypothalamus (n = 78) or the medial preoptic area (n = 29)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
71
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(80 citation statements)
references
References 24 publications
8
71
1
Order By: Relevance
“…Data analysis: Since secretory profiles of GH, GHRH and SRIF were found to be episodic, and pulse detection was done based on the methods reported previously [11,13,23]. A pulse was defined when CVs of assay values composing both ascending and descending phases of each peak exceeded 2 times the corresponding intraassay CV calculated for the pulse detection in each assay.…”
Section: Icv Injection Of Npy Galanin and Ghrelinmentioning
confidence: 99%
“…Data analysis: Since secretory profiles of GH, GHRH and SRIF were found to be episodic, and pulse detection was done based on the methods reported previously [11,13,23]. A pulse was defined when CVs of assay values composing both ascending and descending phases of each peak exceeded 2 times the corresponding intraassay CV calculated for the pulse detection in each assay.…”
Section: Icv Injection Of Npy Galanin and Ghrelinmentioning
confidence: 99%
“…Blood samples (0.3 ml) were taken every 6 min for 2 h through the intra-atrial cannula and an equal volume of heparinized saline containing naloxone (Sigma Chemical Co., St Louis, MO, USA) (0.5 mg/kg per h) or heparinized saline only was replaced after each bleeding (16,17). Rats were divided into three experimental groups: group 1, 3V saline þ i.v.…”
Section: Administration Of 2-b4omentioning
confidence: 99%
“…Funabashi et al (16) reported that, in ovx rats, intermittent administration of naloxone in the same dose as we used resulted in a significant increase in the mean LH concentration. Kimura et al (17) reported that the same intermittent administration of naloxone in ovx rats significantly increased the frequency and the duration of multiunit activity volleys that accompanied the initiation of each LH pulse. In the present study, naloxone did not increase the mean LH concentrations; therefore, the suppressive effect of 2-B4O on the pituitary response to GnRH might not be completely blocked by administration of naloxone.…”
Section: Figurementioning
confidence: 99%
“…Within this region, particular attention has been focused on the arcuate nucleus (ARN) (13,14), where studies have also recorded multiunit activity that correlates with pulsatile LH secretion in a variety of mammals (15)(16)(17)(18). Although the identity of the neural elements giving rise to multiunit activity are unknown, it has been suggested that they may represent the activity of kisspeptin neurons within the ARN (19).…”
mentioning
confidence: 99%